Environmental filters explain the ecomorphological patterns of stream fish in the southern Amazon - Lidia Brasil SEABRA; Giovanni Sampaio PALHETA; Naraiana Loureiro BENONE; Bruno AYRES SANTOS; Luciano Fogaça de Assis MONTAG (Acta Amazonica, 2023)
ABSTRACT The ecomorphology reflects morphological variations that may indicate significant ecological processes. In this study, the influence of environmental variables on the ecomorphological composition of stream fish was tested. The study was developed in ten streams within a conservation area in the Juruena River sub-basin, in Mato Grosso state, Brazil. The sampling occurred during the drought period in July 2012. The fish were sampled with simple sieves and trawl nets. We analyzed 17 variables of the physical habitat and 14 morphological indices based on morphometric measurements of the fish. In total, 753 specimens were collected, comprising four orders, 14 families, and 27 species. Only fine sediments influenced the ecomorphological composition of the fish assemblages. This substrate variable acted as a filter for the ecomorphology of fish that usually inhabit slow waters, have a morphology adapted towards a good stabilization capacity and maneuverability, fins capable of large and rapid impulses, and that feed close to the surface. Our results can contribute to the understanding of the ecological processes that drive the composition of fish assemblages in conserved Amazonian streams.